Alan Gilbert (comp.). Housing and land in urban Mexico. San Diego : University of California, 1989. 189 p. (Monograph series ; 31) - Muñoz Contreras, María Elena (El Colegio de México A.C., 1990)
ALAN GILBERT (comp.), Housing and Land in Urban México, University of California, San Diego, Monograph Series, 31, 1989.